A High-Throughput Assay for Monitoring Ubiquitination in Real Time - Franklin, Tyler G.; Pruneda, Jonathan N. (Frontiers in Chemistry, 2019)
Protein ubiquitination is a highly orchestrated process that controls diverse aspects of human biology. Dysregulation of this process can lead to various disease states including cancer, neurodegeneration, and autoimmunity. It is the correction of these dysregulated pathways, as well as the enticing ability to manipulate protein stability, that have instigated intense research into the therapeutic control of protein ubiquitination. A major bottleneck in the development and validation of small molecule modulators is the availability of a suitable high-throughput assay for enzyme activity. Herein, we present a new assay, which we term UbiReal, that uses fluorescence polarization to monitor all stages of Ub conjugation and deconjugation in real time. We use the assay to validate a chemical inhibitor of the E1 ubiquitin-activating enzyme, as well as to assess the activities and specificities of E2s, E3s, and deubiquitinases. The sensitivity and accessibility of this approach make it an excellent candidate for high-throughput screens of activity modulators, as well as a valuable tool for basic research into the mechanisms of ubiquitin regulation.